“Writing for Healing” Pembuatan Website, Buku, dan Video Edukatif dan Inspiratif untuk Pencegahan, Pengurangan Penularan serta Kecemasan terkait COVID-19 - Nabilla Kusuma Vardhani; Andri Handayani; Cisya Dewantara Nugraha; Dewi Cahya Ambarwati; Erlin Estiana Yuanti; Ghifari Yuristiadhi Masyhari Makhasi; Nur Endah Nugraheni; Tri Nuraniwati; Dian Budi Santoso; Rita Dian Pratiwi; Irkham Huda; Jimmy Trio Putra (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2022)
COVID-19 pandemic has an impact on people's lives in all sectors. Adaptation to go through difficult times is needed so that all parties can survive and find solutions to various difficulties experienced. One way that can be done is by motivating others through writing activities. Karen A. Baikie and Kay Wilhelm (2005) found that writing about traumatic, stressful, and emotional events has an impact on improving physical and psychological health in both clinical and non-clinical populations. Besides, miksilva.com also writes that writing can also heal writers and readers from life pressures and feelings of anxiety. This community service focuses on creating educational and inspiring websites, books, and videos to prevent and reduce transmission and anxiety related to COVID-19. The team took the theme